(NrUSSKIJ QZYK (B:s ((NgRAMMATI^ESKOE U^ENIE O SLOWE(B) : (Nu^EBNOE POSOBIE (B/s - (NwINOGRADOW(B, (NwIKTOR wLADIMIROWI^s ((NmOSKWA (B:s (NwYS[AQ [KOLA (B,s, 1986)
(NbIBLIOGR(B. (NW PRIME^(B. (NW KONCE GLAWs
(NuKAZ(B. (NIMEN(B: (NS(B. 627-631s
Keywords: (NgRAMMATIKAs; (NrUSSKIJ QZYKs; (NsLOWO W RUSSKOM QZYKEs